2000
DOI: 10.1053/euje.2000.0030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pacing-induced Heart Rate Variation on Longitudinal and Circumferential Regional Myocardial Function After Acute Beta-Blockade—a Cardiac Ultrasound Study

Abstract: Changes in systolic velocities and velocity gradients were independent of heart rate reduction under high dosage beta-blockade, whereas wall thickening fraction, mitral valve plane excursion and velocity time integrals changed due to pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Our present findings, using VEL SYS and SR SYS to measure regional myocardial function, are consistent with the known pharmacological effects of dobutamine and high-dose β-blockade on both regional contractile function and global systolic LV function in normal myocardium [4,24,27,28]. During changing contractility conditions in ischaemic myocardium, the motion parameter VEL SYS , but not the deformation parameter SR SYS , paralleled parameters of global contractility.…”
Section: Motion Compared With Deformationsupporting
confidence: 91%
“…Our present findings, using VEL SYS and SR SYS to measure regional myocardial function, are consistent with the known pharmacological effects of dobutamine and high-dose β-blockade on both regional contractile function and global systolic LV function in normal myocardium [4,24,27,28]. During changing contractility conditions in ischaemic myocardium, the motion parameter VEL SYS , but not the deformation parameter SR SYS , paralleled parameters of global contractility.…”
Section: Motion Compared With Deformationsupporting
confidence: 91%
“…In a previous animal study [18], PSV decreased after intravenous β-blockade, and no additional decrement was observed when the animals were paced at heart rates slightly higher than the baseline. On the basis of these findings, the authors [18] concluded that the decrease in PSV was independent of the fall in heart rate induced by β-blockade. This study [18] indicates that the treppe effect on myocardial PSV is small compared with the influence of the sympathetic nervous system on contractility.…”
Section: Table 4 Long-axis Psv and Excursion For Each Of The Left Venmentioning
confidence: 84%
“…On the basis of these findings, the authors [18] concluded that the decrease in PSV was independent of the fall in heart rate induced by β-blockade. This study [18] indicates that the treppe effect on myocardial PSV is small compared with the influence of the sympathetic nervous system on contractility.…”
Section: Table 4 Long-axis Psv and Excursion For Each Of The Left Venmentioning
confidence: 91%
See 1 more Smart Citation
“…However, there are few reports of transthoracic echocardiography of a pig [18,20]. Transthoracic echocardiography of a micropig is technically challenging for several reasons.…”
Section: Discussionmentioning
confidence: 99%